Pengaruh Transfer Pricing, Pajak Tangguhan Dan Pinjaman Antar Perusahaan Afiliasi Terhadap Tax Avoidance - Ivanka Maharani SZ; Agrianti Komalasari; Einde Evana; Kamadie Sumanda Syafiz (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Tax is a mandatory contribution to society, both individual taxpayers and corporate taxpayers to the state. However, taxpayers and business entities often look for ways to reduce the tax burden they have to pay. This is because Indonesia uses a self-assessment system which allows people to cheat in calculating their tax burden. This act of fraud is called tax avoidance. In the practice of tax avoidance there are several types of tricks, some of which are transfer pricing, deferred tax, and loans between affiliated companies. This research aims to determine the extent to which variables namely transfer pricing, deferred tax and loans between affiliated companies influence tax avoidance practices in Indonesia. From the results of several tests carried out in this research, it is stated that transfer pricing and loans between affiliated companies do not have a significant effect on tax avoidance. On the other hand, deferred tax has a significant positive effect on tax avoidance.